Growth, Inequality and Globalization: Theory, History, and Policy by Phillipe Aghion and Jeffery G. Williamson, Cambridge University Press, 1998,207 pp. (American Journal of Islam and Society, 1999)
To what extent is some poverty necessary for economic growth? Doespoverty motivate the poor to work harder, enabling them to both escape theirpoverty and in the process increase the total wealth of society? Or does povertyon balance promote those negative influences such as ill-health and a lack ofproper education that prevent the poor, and hence society, from attaining itsfull wealth potential? What effect does a redistribution of wealth from rich topoor have upon the growth rate? Would the poor manage the extra wealththereby gained in a manner more beneficial for society than when the rich managedit? How does income disparity within an economy wax and wane asgrowth takes place, and how does income disparity between economies changein the face of globalization? Perhaps most important of all, what can politicaleconomists learn from past experiences in informing policy recommendationsfor the future?Such are the questions to which two professors of economics address inGrowth, Inequality and Globalization: Theory, History, and Policy. In the firstof two discussions on the topic, phillipe Aghion from University CollegeLondon adopts a largely mathematical approach. In the second discussion,Jeffery G. Williamson from Harvard undertakes an empirical analysis. Thesetwo approaches compliment one another rather well.Two ideas are generally handed down to the modem student of economicson the relationship between growth and wealth inequality. One is based uponan incentives theory according to which inequality promotes faster growth. Theother derives from the Kuznet's hypothesis which holds that, as an economypasses through a growth phase, inequality first increases and then decreaseswith the onset of maturity. Aghion labels both of these ideas as fallacies, brieflyciting recent evidence which shows widening income inequality in the UnitedStates. His mathematical modeling further shows that, under certain circumstances,increases in inequality (as measured by the increased dispersion ofinvestment holdings among members of the society) can lead to lower growth.This is because the marginal return on investment for the poor is greater thanfor the rich. In plain language, poor people can create more wealth with anadditional unit of investment assets than the rich can. Hence, if the rich haveall the assets, society as a whole may not achieve the highest available returns.In a perfect capital market, the rich could perhaps lend or invest their surplus ...